2018
DOI: 10.1186/s12905-018-0588-y
|View full text |Cite
|
Sign up to set email alerts
|

“It happens to clinicians too”: an Australian prevalence study of intimate partner and family violence against health professionals

Abstract: BackgroundThe purpose of this study was to measure the prevalence of intimate partner and family violence amongst a population of Australian female nurses, doctors and allied health professionals.MethodsWe conducted a descriptive, cross-sectional survey in a large Australian tertiary maternity hospital with 471 participating female health professionals (45.0% response rate). The primary outcome measures were 12 month and lifetime prevalence of intimate partner violence (Composite Abuse Scale) and family violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 32 publications
5
55
1
Order By: Relevance
“…Having a commitment through personal experience is demonstrated in an Australian study where survivor staff were shown to 'go the extra mile' by attending training and providing clinical practice of a high standard. [73] Motivation through a rights-based belief system [34] is also an untapped area to assist practitioners to become ready to do this work. This area could be explored more as many survivors including Indigenous Peoples and other socially disadvantaged ethnic minorities are further entrapped by health inequities of poverty, racism, colonisation and discrimination because of sexuality, gender and disability.…”
Section: Discussionmentioning
confidence: 99%
“…Having a commitment through personal experience is demonstrated in an Australian study where survivor staff were shown to 'go the extra mile' by attending training and providing clinical practice of a high standard. [73] Motivation through a rights-based belief system [34] is also an untapped area to assist practitioners to become ready to do this work. This area could be explored more as many survivors including Indigenous Peoples and other socially disadvantaged ethnic minorities are further entrapped by health inequities of poverty, racism, colonisation and discrimination because of sexuality, gender and disability.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has noted that female health care staff score significantly higher than their male counterparts in understanding abusive relationships and that women show a preference for female staff, significantly staff who are empathetic and compassionate . Staff with lived experience of IPV may also be beneficial in supporting women . While female staff, or those with lived experience, may be unavailable to attend to women presenting with IPV, appropriate attitudes and knowledge remain key to effective detection and communication with women.…”
Section: Discussionmentioning
confidence: 99%
“…While our research indicates that health professionals take responsibility for their emotional well‐being, the study has also highlighted the importance of workplace‐based confidential counseling and leave for staff who are experiencing IPV. The prevalence of IPV among health professionals been found to be higher than that in the general population, calling for health workplace policies and protocols to acknowledge this common trauma . The Royal Women's Hospital in Victoria, Australia, has, for example, established a new program “Strengthening Hospital Responses to Family Violence” that provides training for health care workers to support both staff and patients.…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis we created a binary variable where a score of 0 represented no experience had occurred, whereas a score of 1 identified at least 1 item was checked. 7,42 The following variables were included in the study to serve as potential predictors or correlates of IPV.…”
Section: Methodsmentioning
confidence: 99%
“…IPV among physicians is seldom acknowledged or assessed. 6 , 7 Physicians report IPV prevalence between 6% and 24% (women 7%-24%, men 6%-10%), but studies have limited generalizability due to lack of standardized and validated measures, small sample sizes, dated information, and sampling frames that combine child abuse plus partner abuse, or combine nursing, student, and physicians, or only survey women. 8 - 12 Almost all physician IPV studies utilize self-report of self-defined partner or domestic abuse.…”
Section: Introductionmentioning
confidence: 99%